Upaya Preventif Transmisi Covid-19 di Desa Tirtomarto, Kecamatan Ampelgading, Kabupaten Malang, Jawa Timur - Putri, Santy Irene; Akri, Yusnita Julyarni; Yunamawan, Donny (Universitas Nusantara PGRI Kediri, 2022)
The increasing number of Covid-19 cases is a challenge for the government, both at the central and regional levels. Tirtomarto Village is one of the villages in Malang Regency, East Java with a level of community compliance that is still not fully disciplined in implementing health protocols. Wearing a mask and washing your hands can slow the spread of the Covid-19 virus. Therefore, real action is needed to increase public awareness of the importance of using masks and hands-on sanitizers to prevent the transmission of Covid-19. WHO recommends alcohol-based hand sanitizers (hand sanitizers) for hand hygiene. This activity aims to encourage public awareness in Tirtomarto Village in implementing efforts to prevent the transmission of Covid-19 through the provision of masks specifically aimed at underprivileged people. The partnership program evaluation activity was carried out through monitoring the process of distributing masks to the community in Tirtomarto Village by confirming the village head on the following day. Based on the monitoring and evaluation carried out by the team, information was obtained that masks were evenly distributed among residents of Tirtomarto Village, Ampelgading District, Malang Regency.